2016
DOI: 10.1111/all.12991
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus‐specific antibody responses in preschool children with acute wheeze reflect severity of respiratory symptoms

Abstract: Antibody response to recombinant RV VP1 proteins was associated with longer time with respiratory symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 25 publications
(36 reference statements)
2
48
0
Order By: Relevance
“…Viral infections are the most frequent cause behind the wheezing symptom. In recent reports on preschool children presenting at the hospital with acute wheeze, RV was detected in almost 70% of them . Despite its high prevalence, there is a lack of evidence and mixed results regarding the pharmacological treatment .…”
Section: Preschool Wheezementioning
confidence: 99%
“…Viral infections are the most frequent cause behind the wheezing symptom. In recent reports on preschool children presenting at the hospital with acute wheeze, RV was detected in almost 70% of them . Despite its high prevalence, there is a lack of evidence and mixed results regarding the pharmacological treatment .…”
Section: Preschool Wheezementioning
confidence: 99%
“…Moreover, it has been found that the natural immune response towards rhinovirus, the most common asthma-triggering respiratory virus, is directed against an N-terminal peptide of the VP1 coat protein [30]. It has therefore become possible to detect rhinovirus infections by measuring specific antibody responses against this VP1 peptide [31][32][33].…”
Section: Protein Biomarkers and Their Role In Asthmamentioning
confidence: 99%
“…New forms of molecular biology tests, based on molecular cloning, have been proposed for determination of diseases caused by allergen molecules and respiratory virus infections in routine practice, which allow distinguishing and separating those groups of patients. For example, for identifying causative rhinovirus groups, measurement of antibodies towards N-terminal fragments of the human rhinovirus coat protein VP1 can be useful [31,32]. Specific IgE towards single allergen molecules or complex IgE and IgG reactivity profiles can be biomarkers and even predictors of allergic asthma.…”
Section: Biomarkers In Phenotyping and Endotyping Of Asthmamentioning
confidence: 99%
See 2 more Smart Citations